AGROWISATA NANAS DESA MADU SARI KABUPATEN KUBU RAYA - Fannisaningrum, Rahmi; Alhamdani, Muhammad Ridha; Nurhamsyah, Muhammad (JMARS: Jurnal Mosaik Arsitektur, 2024)
Madu Sari Village is a village in Sungai Raya District that has a large area of land in the form of peat, with the potential to become a village that produces horticultural commodities. Madu Sari Village can supply ±600 pineapples per week when it is not in season and ±2,000 pineapples per week when it is in season. This village can be further developed to become an agrotourism destination. The formulation of the problem for this final assignment is "What are the facilities needed and their design to realize pineapple agrotourism in Madu Sari Village, Kubu Raya Regency, as an agrotourism-based tourism destination?" The aim of designing this final project is to develop a design concept that can be used as a reference for the development of effective and efficient agrotourism to accommodate activities and provide tourist facilities. The design method used in solving problems in agrotourism design uses the five-step design process method in the book "Introduction to Architecture" (Snyder and Catanese, 1984). Referring to the potential and existing conditions of the area, the site concept was developed through the Open Space concept, which resulted in a building design consisting of three regional zones, namely the reception zone, recreation zone, and education zone. The results of this design are expected to have an impact on the community, especially pineapple farmers in Madu Sari Village, as well as improving the economy and pineapple cultivation as a tourism development in Kubu Raya Regency in the form of a design reference based on human potential, site potential, and natural potential.